Local Importance of Wild Woody Plants for Medicinal Use in the Tchambi Region; Maniema (DR Congo) - USSENI NASIBU, Hilaire; KAPOLI OMBA, Dan; NGONGO LUSHIMA, Jean-Pierre; YAKAYENGO TOKO, Augustin; YUMA MADJALIWA, Pierre; MBAYU MPANYA, Faustin; MUKANDAMA NDOLANDOLA, Jean-Pierre; LISINGO WA LISINGO, Janvier; LOMBA BOSOMBO, Christophe; NSHIMBA SEYA, Hippolyte (European Journal of Science, Innovation and Technology, 2025)
The contribution of trees to food security and primary healthcare in African societies is well established. The objective of the study was to investigate the diversity and local importance of woody plants used in traditional medicine in Tchambi. Data collection was based on ethnobotanical surveys of 80 traditional practitioners living in ten villages in the peripheral areas of Lomami National Park. Data analysis consisted of calculating medicinal use values ​​and Sorensen’s similarity index, the Kh2 test of independence and correlation between the number of organs used and the number of diseases treated for a plant. A total of 42 species belonging to 21 families were identified. Millettia versicolor (Med. Uvs = 0.46), Autranella congolensis (Med. Uvs = 0.42), Alstonia bonnei (Med. Uvs = 0.39), Bridelia micrantha (Med. Uvs = 0.37), Pentaclethra macrophylla (Med. Uvs = 0.36) and Piptadeniastrum africanum (Med. Uvs = 0.23) are the most useful species in the area following their Med. UVS. The Chi-square test showed that the population’s perception of the availability of medicinal species was influenced by age; while the correlation test showed that there is a moderate positive correlation between the number of organs used for a plant and the number of diseases it can treat (T = 0.558, p-value = 0.000). The more a plant is used for several organs at the same time, the more it can treat multiple diseases.